Acquisition of Agricultural Lands (Legal Studies on Central Europe, 2022)
The book series Legal Studies on Central Europe seeks to publish comparative legal scholarship on a wide variety of topics. The primary goal of the series is to present and address legal issues which arise in connection with the Central European region, taking into account the legal traditions, culture and approach of the countries therein. The series consists and will consist of titles on not only private and public law but also legal and integration history. Furthermore, it aims to encompass titles which deal with and analyse international law and EU law aspects related to the countries in the Central European region. The books published in the series are written for both academics and legal practitioners who are interested in contemporary legal problems connected to Central European countries.